EPILEPSY AND RISK OF SUICIDE (A REVIEW) - O. A. Pylaeva; K. Yu. Mukhin; A. A. Shatenshteyn (Русский журнал детской неврологии)
The authors propose a fundamental review, devoted to the factors, wich increase the risk of suicidal behavior (suicidal ideation and suicide attempts) in patients with epilepsy. It is known, that suicidal risk is increased 5 times more in patients with epilepsy, and 25 times more in patients with temporal lobe epilepsy and complex focal seizures, than in general population. The main factors, increasing suicidal risk in epilepsy, are comorbid affective disorders (depression), and psychosis. The authors also describe the role of antiepileptic drugs.